Transient Analysis of Coupled Natural Convection and Surface Thermal Radiation in a Tilted Open Cavity (Journal of Advanced Thermal Science Research, 2015)
Numeric results of the transient heat transfer by natural convection and surface thermal radiation in a tilted open cavity are presented. The conservation equations in primitive variables are solved using the finite volume method and the SIMPLEC algorithm. The transient results are obtained for a Rayleigh number of 106 and five inclination angles (0°, 45°, 90°, 120° and 180°. The numerical model predicts flow instabilities for inclination angle of 0°, which avoids reaching the steady state. The steady state is reached after a long time for ϕ=180°.
Keywords: Open cavity; transient natural convection; thermal radiation